Understanding factors for investment into South African diaspora bonds: an extended theory of planned behaviour - Kader, Faatimah (Graduate School of Business (GSB), 2025)
South Africa's power infrastructure faces a multi-faceted crisis linked to electricity supply, ageing infrastructure and a concentration of coal-based production, as well as shortfalls in financing infrastructure development. Diaspora bonds offer a promising alternative financing mechanism for infrastructure development in emerging markets like South Africa. This study explores investor demand for South African diaspora bonds, employing thematic analysis within an extended Theory of Planned Behaviour framework. The research entailed semi-structured interviews with 11 individuals from the South African diaspora based in the USA, UK, and Australia. The results of the thematic analysis reveal that attitudinal, social, ability and environmental perceptions towards investing into South African diaspora bonds are largely shaped by conditionalities pertaining to risk and benefit realisation. Further economic, institutional and regulatory reform is needed to attract investors towards South African diaspora bonds. The main attitudinal motives are underpinned by (i) patriotism with varying conditionalities, (ii) risk perception, (iii) corruption, governance and institutions, (iv) return expectations and (v) informational advantages. The participants were more inclined to invest for patriotic reasons on condition that personal welfare benefits are realised if a return to South Africa is planned, and/ or investment exposure was limited relative to the perceived risk. The participants perceived a heightened risk, in terms of credit default risk, due to corruption and inadequacies in the rollout of infrastructure projects, as well as currency risk, especially when not planning to return to South Africa. However, a positive risk perception relating to asset class diversification and the ability to offset rand-denominated liabilities in South Africa was observed. From a governance, institutions and corruption standpoint, the participants were concerned about government service delivery, misappropriation of funds, poor international relations, as well as corruption in procurement, weak institutions, and government policies deterring FDI; however, they had confidence in the regulatory bodies, governing financial instruments. Some participants were willing to accept a low return based on patriotism; however, this was conditional, as these investors were seeking limited exposure, and intent on returning to South Africa, in the hope that the bond would improve infrastructure. Other participants had expectations of a high return, due to the perceived high risk, or planned to base the return on the collective of the costs and benefits. Informational advantages were also observed to result in a poor sentiment of South Africa in general, with the participants preferring international geographies for investment purposes. The main social perception was that South African diaspora bonds may be a high-risk investment, largely informed by opinions and guidance offered by friends and family members with investment experience and/ or living in South Africa, investment managers, and partners often with shared finances. In terms of ability to invest into South African diaspora bonds and/ or Perceived Behavioural Control, enablers and disablers were identified. The main enablers include: (i) sufficiency in disposable income, (ii) technology as a means to streamline investment processes, and (iii) adequacy in investment knowledge. The primary disablers observed were: (i) limitations on current mandatory investment schemes, (ii) insufficient disposable income due to retirement or being employed part-time, (iii) limited knowledge on diaspora bonds and renewable energy, and (iv) bottlenecks in international fund flows. The primary environmental motives emanating from the research are: (i) Satisfaction, (ii) Policy Influence and (iii) interest in the underlying asset. The findings indicated that satisfaction played a role, when the participants linked the investment to supporting the welfare of South Africa. Additionally, the research revealed that the participants may be incentivised through policy such as tax incentives, improvements in procurement processes, resource allocation, and improved diaspora engagement amongst others. This research further finds that respondent interest in green finance, as well as the improvement of the electricity infrastructure, may play a role in driving investment into a South African diaspora bond. Based on these results, recommendations pertaining to the research include targeting the South African diaspora bond at the diaspora intending to return to South Africa. The findings further suggest that engagement with the South African diaspora need to be strengthened. Additionally, the South African diaspora bond should ideally be implemented through streamlined systems-based platforms that offer transparency, auditability, and accountability. The investment should also be embedded in collaboration with established investment managers, and partnerships with the private sector should be forged, to strengthen controls relating to the lack of confidence in the public sector. Another consideration is to issue the South African diaspora bond in a universal hard currency, as well as mitigate the foreign exchange risk by means of a currency swap. Further research may be required to support this current research, covering the issuer perspective, and other countries of adoption by diaspora, not otherwise covered within this research.